Bone marrow sarcoidosis associated with long‐term interferon‐β treatment for multiple sclerosis. Issue 11 (27th September 2016) - Teh, Angela; Russell, Patrick; Li, Jordan; Hewage, Udul
Key Clinical Message: Sarcoidosis is a diagnosis that should be considered in patients receiving interferon therapy, who present with anemia and multiorgan dysfunction regardless of the duration of their treatment. When sarcoidosis is suspected, bone marrow biopsy should be considered especially for cases predominant by extrapulmonary features. Abstract : Sarcoidosis is a diagnosis that should be considered in patients receiving interferon therapy, who present with anemia and multiorgan dysfunction regardless of the duration of their treatment. When sarcoidosis is suspected, bone marrow biopsy should be considered especially for cases predominant by extrapulmonary features.